Oblicz wartości liczbowe następujących wyrażeń algebraicznych

a) (½a + 2b) (-3) dla a= -4,b= -½
b)(-4ab+3)² dla a= - ⅛,b=4
c)2a² - 4b dla a=½,b=⅛
d)2/3p² -2q³ dla p=6,q= -1
e)x² -3xy +4y -2 dla x=-2,y= ½
f) (4x-2y)³ dla x= -1/8,y=1/4
g) (¾m - 4n²) (p²-½) dla m= -2/3,n= -½,p=1

3

Odpowiedzi

2010-04-06T13:00:31+02:00
A) (½a + 2b) (-3) dla a= -4,b= -½
(½*(-4)+2*(-½)(-3)=(-2-1)(-3)=-3*(-3)=9

b)(-4ab+3)² dla a= - ⅛,b=4
(-4*(-⅛)*4)²=2²=4

c)2a² - 4b dla a=½,b=⅛
2*(½)²-4*⅛=2*¼-½=½-½=0

d)2/3p² -2q³ dla p=6,q= -1
⅔*6²-2*(-1)³=⅔*36-2*(-1)=24+2=26

e)x² -3xy +4y -2 dla x=-2,y= ½
(-2)²-3*(-2)*(½)+4*½-2=4+3+2=9

f) (4x-2y)³ dla x= -1/8,y=1/4
(4*(-⅛)-2*¼)³=(-½-½)³=(-1)³=-1

g) (¾m - 4n²) (p²-½) dla m= -2/3,n= -½,p=1
(¾*(-⅔)-4*(-½)²)(1²-½)=(-½-1)*½= - ³/₂*½=-¾
2 4 2
2010-04-06T13:13:33+02:00
A) (½a + 2b) (-3) dla a= -4,b= -½
-3/2a - 6b = -3/2 x (-4) - 6 x (-1/2) = 12/2 + 6/2 = 6 + 3 = 9

b)(-4ab+3)² dla a= - ⅛,b=4
(-4 x -1/8 x 4 + 3)² = (16/8 + 3)² = 5² = 25

c)2a² - 4b dla a=½,b=⅛
2 x 1/4 - 4/8 = 2/4 - 4/8 = 4/8 - 4/8 = 0

d)2/3p² -2q³ dla p=6,q= -1
2/3 x 6² - 2 x (-1)³ = 2/3 x 36 + 2 = 36/3 + 2 = 14

e)x² -3xy +4y -2 dla x=-2,y= ½
(-2)² - 3 x (-2) x 1/2 + 4 x 1/2 - 2 = 4 + 3 + 2 - 2 = 7

f) (4x-2y)³ dla x= -1/8,y=1/4
(-4/8 - 2/4)³ = (-2/4 - 2/4)³ = (-4/4)³ = -1

g) (¾m - 4n²) (p²-½) dla m= -2/3,n= -½,p=1
(-6/12 - 4 x 1/4) (1 - 1/2) = (-1/2 -1) (1/2) = -3/2 x 1/2 = -2/2 = -1
2010-04-06T14:07:34+02:00
A)
(½a + 2b) (-3) =
-1½a-6b =
-1½*(-4)-6*(-½) =
6+3 =
9


b)
(-4ab+3)² =
(-4*(-⅛)*4+3)² =
(2+3)² =
5² =
25


c)
2a² - 4b =
2*(½)²-4*⅛ =
2*¼-½ =
½-½ =
0


d)
⅔p² -2q³ =
⅔*6²-2*(-1)³ =
⅔*36-2*(-1) =
24+2 =
26


e)
x² -3xy +4y -2 =
(-2)²-3*(-2)*½+4*½-2 =
4+3+2-2 =
7


f)
(4x-2y)³ =
(4*(-⅛)-2*¼)³ =
(-½-½)³ =
(-1)³ =
-1


g)
(¾m - 4n²) (p²-½) =
(¾*(-⅔)-4*(-½)²(1²-½) =
(-½-4*¼)(1-½) =
(-½-1)(½) =
(-1½)(½) =